Remedies of specific performance for land contracts: Legal development - Mohamad, Nor Asiah; Syed Abdul Kader, Sharifah Zubaidah (Ministry of Finance Malaysia, 2018)
This paper discusses the relief of specific performance (SP) and deals with types and nature of contracts that may be ordered by the court to be specifically performed and those that cannot be specifically performed. Specifically, this paper analyses the circumstances in which the courts decide to grant SP and not to grant SP for land contract. Under the law the remedy of SP is discretionary, and such discretion is to be exercised according to well established principles. Employing doctrinal legal research, this study analyses the relevant provisions under the Specific Relief Act 1950 and identifies how the courts applied the provisions to case laws thus developing a precedent on SP for immoveable property. It is found out that the right to sue for specific performance in equity is quite distinct from a cause of action at common law. Specific performance is granted when there are circumstances justifying it. The grant of SP is always subject to conditions. SP is said to be the best remedy for breach of contract for immoveable property. For example, land is normally deemed by the law to have a special value, the loss of which may not be adequately measured or compensated by damages or money (S 11(2) of the Act) unless and until the contrary is performed. All the above must be read subject to section 20 of the same Act that provides for circumstances where SP cannot be granted.